Role of government financial support and vulnerability characteristics associated with food insecurity during the COVID-19 pandemic among young Peruvians - Curi-Quinto, K; Sánchez, A; Lago-Berrocal, N; Penny, ME; Murray, C; Nunes, R; Favara, M; Wijeyesekera, A; Lovegrove, JA; Soto-Cáceres, V; Vimaleswaran, KS (MDPI, 2021)
Peruvian households have experienced one of the most prevalent economic shocks due to COVID-19, significantly increasing their vulnerability to food insecurity (FI). To understand the vulnerability characteristics of these households among the Peruvian young population, including the role of the government’s response through emergency cash transfer, we analysed longitudinal data from the Young Lives study (n = 2026), a study that follows the livelihoods of two birth cohorts currently aged 18 to 27 years old. FI was assessed using the Food Insecurity Experience Scale. Household characteristics were collected before and during the COVID-19 outbreak in Peru to characterise participants’ vulnerability to FI. Multivariate logistic regression was used to evaluate the association between government support and participants’ vulnerability characteristics to FI. During the period under study (March to December 2020), 24% (95% CI: 22.1–25.9%) of the participants experienced FI. Families in the top wealth tercile were 49% less likely to experience FI. Larger families (>5 members) and those with increased household expenses and decreased income due to COVID-19 were more likely to experience FI (by 35%, 39% and 42%, respectively). There was no significant association between government support and FI (p = 0.768). We conclude that pre-pandemic socioeconomic status, family size, and the economic disruption during COVID-19 contribute to the risk of FI among the Peruvian young population, while government support insufficiently curtailed the risk to these households.